2016
DOI: 10.1007/s00170-016-8967-8
|View full text |Cite
|
Sign up to set email alerts
|

Machinability analysis of dry drilling of carbon/epoxy composites: cases of exit delamination and cylindricity error

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…10a and b. The same results have been reported by Srinivasan et al [40] in optimizing the delamination factor in GFRP composites and Ameur et al [41] in conducting machinability analysis of carbon fiber composites to understand the exit delamination and cylindricity errors. The exit delamination generally presents as a crack in the direction of the fibers Fig.…”
Section: Effect Of Thrust Force On Drilling Parameterssupporting
confidence: 68%
“…10a and b. The same results have been reported by Srinivasan et al [40] in optimizing the delamination factor in GFRP composites and Ameur et al [41] in conducting machinability analysis of carbon fiber composites to understand the exit delamination and cylindricity errors. The exit delamination generally presents as a crack in the direction of the fibers Fig.…”
Section: Effect Of Thrust Force On Drilling Parameterssupporting
confidence: 68%
“…where Di is the drill bit diameter in mm, F is the feedrate in mm/min. To control the diameters quality, measurements were taken on 24 points along the circumference of the hole (as considered a suitable number [32]) by a coordinate measuring machine, Mitutoyo BX 303. The least square circle method was used to calculate the diameter measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental results obtained by Ameur et al. 35 indicated that when dry drilling of carbon/epoxy composites using twist-WC carbide, HSS, and TiN-coated carbide drill at various spindle speeds and feed rates, coated carbide drills are the most effective in drilling of composites because of less thrust force induced. And drilling at 60 mm/min of feed rate, 3000 rev/min of spindle speed, and WC-TiN carbide drill was recommended for minimal delamination factor at exit, cylindricity error, thrust force, and torque.…”
Section: Effect Of Tool Geometry and Materialsmentioning
confidence: 99%